Decidualization of human endometrial stromal cells requires steroid receptor coactivator-3 - Maurya, Vineet K.; Szwarc, Maria M.; Lonard, David M.; Gibbons, William E.; Wu, San-Pin; O’Malley, Bert W.; DeMayo, Francesco J.; Lydon, John P. (Frontiers in Reproductive Health, 2022)
Steroid receptor coactivator-3 is a member of the multifunctional p160/SRC family of coactivators, which also includes SRC-1 and SRC-2. Clinical and cell-based studies as well as investigations on mice have demonstrated pivotal roles for each SRC in numerous physiological and pathophysiological contexts, underscoring their functional pleiotropy. We previously demonstrated the critical involvement of SRC-2 in murine embryo implantation as well as in human endometrial stromal cell (HESC) decidualization, a cellular transformation process required for trophoblast invasion and ultimately placentation. We show here that, like SRC-2, SRC-3 is expressed in the epithelial and stromal cellular compartments of the human endometrium during the proliferative and secretory phase of the menstrual cycle as well as in cultured HESCs. We also found that SRC-3 depletion in cultured HESCs results in a significant attenuation in the induction of a wide-range of established biomarkers of decidualization, despite exposure of these cells to a deciduogenic stimulus. These molecular findings are supported at the cellular level by the inability of HESCs to morphologically transform from a stromal fibroblastoid cell to an epithelioid decidual cell when endogenous SRC-3 levels are markedly reduced. To identify genes, signaling pathways and networks that are controlled by SRC-3 and potentially important for hormone-dependent decidualization, we performed RNA-sequencing on HESCs in which SRC-3 levels were significantly reduced at the time of administering the deciduogenic stimulus. Comparing HESC controls with HESCs deficient in SRC-3, gene enrichment analysis of the differentially expressed gene set revealed an overrepresentation of genes involved in chromatin remodeling, cell proliferation/motility, and programmed cell death. These results were confirmed by the demonstration that SRC-3 is required for the expansion, migratory and invasive activities of the HESC population, cellular properties that are required in vivo in the formation or functioning of the decidua. Collectively, our results support SRC-3 as an important coregulator in HESC decidualization. Since perturbation of normal homeostatic levels of SRC-3 is linked with common gynecological disorders diagnosed in reproductive age women, this endometrial coregulator may open novel clinical avenues in the diagnosis and/or treatment of a non-receptive endometrium, particularly in patients presenting non-aneuploid early pregnancy loss.